Supraglacial lake outlines and depth estimation in Northeast Greenland from 2016 to 2022 - Katrina Lutz; Philipp Hochreuther; Matthias Holger Braun; Niklas Neckel; Nathalie Reimann; Angelika Humbert (PANGAEA, 2024)
This dataset contains supraglacial lake outlines derived from Sentinel-2 optical imagery over the 2016 to 2022 summer melt seasons. These outlines span a region cover around 82,000 km2 over Nioghalvfjerdsbrae (79N Glacier) and Zachariæ Isstrøm in Northeast Greenland. These outlines were derived using the methodology described in Hochreuther et al., 2021 (https://doi.org/10.3390/rs13020205). This method is based on a red-blue threshold with an integrated shadow-masking algorithm. These masks provide a near-daily time series of supraglacial lake development over these seven years.
In: Lutz, K et al. (2024): Supraglacial lake outlines and depth estimation in Northeast Greenland from 2016 to 2022 using a thresholding method and radiative transfer equation [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.973242